In Search of Meaning Ludwig Wittgenstein on Ethics, Mysticism and Religion - Arnswald, Ulrich (EUKLID : Europäische Kultur und Ideengeschichte. Studien, 2009)
The essays collected in this volume explore some of the themes that have been at the centre of recent debates within Wittgensteinian scholarship. In opposition to what we are tentatively inclined to think, the articles of this volume invite us to understand that our need to grasp the essence of ethical and religious thought and language will not be achieved by metaphysical theories expounded from such a point of view, but by focusing on our everyday forms of expression.